Juventudes e escola na cultura contemporânea – análise do discurso de professores em Weblogs - Lopes, Marilane Silva (2014)
Research under this title and the School in Contemporary Youth Culture - Analysis of Discourse in Teacher Weblogs aims to understand the speech of teachers on the relationship between school and youths in the contemporary world, analyzing the political productivity of such discourse and its possible repercussions on educational practices. Furthermore, this study discusses from the speech of teachers, as the process of mobilizing the student subject to its connection with knowledge occurs, as well as the effects of meaning that these educational discourses take before interpreting the gestures of the subject’s learners. Also aims to analyze the relations between youths and school in the contemporary world, in order to unravel the cultural hybridity that is inherent to the ways of being and acting of the young, questioning its impact on classroom practices. Finally, this research aims to discuss the impacts suffered by the educational field from the place they occupy the youths in the emergence of socialization of young public school in Brazil. It is through discourse analysis (the bias of French Discourse Analysis - Pêcheux) teachers' weblogs that unmask how they hid, construct meaning about the relationship of the school in the contemporary world.